2020
DOI: 10.4322/2179-443x.0667
|View full text |Cite
|
Sign up to set email alerts
|

Hydroalcoholic extract of leaves of Arrabidaea brachypoda (DC.) Bureau present antispasmodic activity mediated through calcium influx blockage

Abstract: Aim: Since other species of the Bignoniaceae Family presented of antispasmodic activity, it was decided, by chemotaxonomic criterion, to determine the antispasmodic activity of the leaves of Arrabidaea brachypoda. Methodology: the segments of the rat jejunum were suspended in glass vats containing specific saline solution, at an appropriate temperature, and after stabilization period, were stimulated by a contractile agent to observe the inhibitory or relaxing effect of EH-FAB. Results: EH-FAB showed the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
3
0
2
Order By: Relevance
“…Fridericia chica (synonym Arrabidaea chica) leaves are usually employed as a red dye, in fact, it has traditionally been used by Sinu artisans of the Colombian Caribbean to make the vueltiao hat [2]. The red color obtained from F. chica comes from anthocyanidins, a class of phenolic compounds with known antioxidant properties [3], and extracts from the plant have shown pharmacological activities linked to beneficial health effects, including anti-inflammatory [4], antiproliferative [5], wound healing [6], antispasmodic [7], photoprotective [8], and leishmanicidal [9] activities. Many of these properties are attributed to different flavonoid compounds reported in F. chica, such as isoscutellarein, 6-hydroxyluteolin, hispidulin, scutellarein, luteolin, apigenin, and hispidulin [10], this last a potential compound for neuroinflammation inhibition [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fridericia chica (synonym Arrabidaea chica) leaves are usually employed as a red dye, in fact, it has traditionally been used by Sinu artisans of the Colombian Caribbean to make the vueltiao hat [2]. The red color obtained from F. chica comes from anthocyanidins, a class of phenolic compounds with known antioxidant properties [3], and extracts from the plant have shown pharmacological activities linked to beneficial health effects, including anti-inflammatory [4], antiproliferative [5], wound healing [6], antispasmodic [7], photoprotective [8], and leishmanicidal [9] activities. Many of these properties are attributed to different flavonoid compounds reported in F. chica, such as isoscutellarein, 6-hydroxyluteolin, hispidulin, scutellarein, luteolin, apigenin, and hispidulin [10], this last a potential compound for neuroinflammation inhibition [11].…”
Section: Introductionmentioning
confidence: 99%
“…EH-FAB inhibited the contraction and relaxation of isolated rat jejunum in a significant and concentration-dependent manner. The authors also observed the significant relaxation of the rat jejunum when it was precontracted by high concentrations of extracellular potassium, demonstrating the participation of the potassium channel in the relaxation mechanism of EH-FAB, and this further shifted the CaCl 2 curve to the right, with a decrease in the maximal effect that is characteristic of the CaV inhibition of the calcium influx [31].…”
Section: Main Chemical Composition Of a Brachypodamentioning
confidence: 82%
“…A phenylethanoid glycoside, namely conadroside (24) was isolated from leaves of A. brachypoda by Bertanha et al [30]. The chemical characterization of the leaves extract revealed the presence of flavonoids apigenin (25), luteolin (26), isoquercitrin (27), rutin (28); furthermore, four chalcones were isolated from the flowers, namely 4 -hydroxy-3-4-dimethoxy-chalcone (29), 3 -hydroxy-3acetate, 4-methoxy-chalcones (30), 3 ,4 -dihydroxy, 3,4,4 -trimethoxy-chalcone (31), and 3,4-dimethoxy-chalcone (32) [31][32][33]. Bio-Pharmacological Properties of A. brachypoda This is one of the species most studied by our research group.…”
Section: Main Chemical Composition Of a Brachypodamentioning
confidence: 99%
“…Estudos rescente com F. platyphylla descrevem sobre a presença de óleo essencial nas flores (Menezes Filho, 2020), flavonol rutina nas folhas (Lima, 2018), cirsimaritina, cirsiliol, hispidulina e 3 ',4'-hiidroxi-5,6,7-trimetoxiflavona (Alcerito et al, 2002;Patel;Patel, 2017), apigenina, luteolina, hispidulina, cirsiliol, 7-metoxipigenina-6-C-hexose, 7-metoxiliteolina-6-C-hexose, isoquercetina, apigenina-6-C-hexose, 8-C-hexose, rutina e arrabidosídeo A (Monteiro et al, 2020), e dois importantes flavonoides braquidinas A, B e C isolados do extrato hidroetanólico das raízes (Rocha et al, 2014;Nunes et al, 2020).…”
Section: Introductionunclassified